Sistem Informasi Pengolahan Data Kepariwisataan Dinas Kebudayaan dan Pariwisata Kabupaten Bintan Berbasis Web - Rahmad Abdul Rahmad; Dwi Nurul Huda; Ahmad Kriswantoro (Jurnal Bangkit Indonesia, 2023)
Abstract— This tourism information system was built with the aim of fulfilling user needs to assist the Bintan Regency Culture and Tourism Office in presenting tourism information on Bintan Island. In this case, there are various problems that have not been optimal from an internal and external perspective in terms of presenting and managing existing tourism information. So with that, the author tries to create a web-based information system that is more attractive so that it is easily accepted and becomes an attraction for users to visit tourism destinations on Bintan Island. The method used in this study uses the waterfall method, this method includes needs analysis, system design, implementation, testing phase, and maintenance, followed by creating a website using the PHP programming language with the codeigniter and boostrap frameworks to produce an attractive and dynamic web appearance and database. MySQL as database. The results of this tourism data processing information system research are expected to assist entrepreneurs or tour managers in promoting and managing their tourism business independently and this system is expected to make it easier for tourists to obtain information. Keywords— information system, data processing, tourism, website.